Antistatic automotive trim PVC (polyvinyl chloride) material and preparation method thereof
A PVC material with a cross-linked network structure addresses the deficiencies of existing automotive interior materials by providing superior antibacterial, anti-aging, and antistatic properties, enhancing mechanical strength and thermal stability.
Patent Information
- Application Number
- CN202411406990.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing PVC materials used in automotive interiors fail to meet the increasing demands for antistatic properties, mildew and antibacterial properties, aging resistance, and moisture resistance.
A PVC material formulation comprising PVC resin, thermoplastic polyurethane, modified filler, plasticizer, auxiliary agent, stabilizer, and cross-linking agent, where the modified filler is prepared by mixing inorganic fillers with a coupling agent and specific additives to form a cross-linked three-dimensional network structure, enhancing antibacterial, anti-aging, waterproof, and antistatic properties.
The formulation results in a PVC material with improved antibacterial, anti-aging, waterproof, and antistatic properties, ensuring enhanced mechanical strength and thermal stability.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of automobile interior decoration materials, and in particular, relates to an antistatic automobile interior decoration PVC material and a preparation method thereof. Background Art
[0002] The interior parts of a car generally refer to the car compartment partitions, door trim panels, dashboard assemblies, armrests, carpets and other parts and materials. For cars, although the interior parts are only some auxiliary parts, they have to assume the functions of mildew and antibacterial, flame retardant and smoke suppression, heat insulation and sound absorption, anti-aging, etc., which play a very important role in the comfort of the car.
[0003] Polyvinyl chloride (PVC) resin is a polar non-crystalline polymer. Its products have good physical and chemical properties and can be widely used in industries, construction, agriculture and daily necessities. PVC composite materials are widely used in automotive interior materials due to their wear resistance and low price, especially in the production of car seats, car door embedded panels, car roofs and sun visors. With the development of society and the improvement of people's quality of life, people's requirements for automotive interior parts are getting higher and higher. Ordinary PVC composite materials can no longer meet people's quality requirements for automotive interior parts in terms of antistatic properties, mildew and antibacterial properties, aging resistance, moisture resistance, etc. Therefore, it is urgent to develop a PVC material with excellent comprehensive properties such as excellent antistatic properties, excellent mildew and antibacterial properties, excellent aging resistance, and good moisture resistance to meet people's increasing quality requirements for automotive interior parts. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide an antistatic automobile interior PVC material and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions: An antistatic automobile interior PVC material comprises the following raw materials in parts by weight: 90-100 parts of PVC resin, 10-20 parts of thermoplastic polyurethane, 48-64 parts of modified filler, 30-40 parts of plasticizer, 2-4 parts of auxiliary agent, 0.5-1 part of stabilizer, 0.5-0.8 part of processing aid and 0.05-0.1 part of cross-linking agent.
[0006] Furthermore, the modified filler is prepared by the following steps: The inorganic filler and deionized water were fully stirred in a beaker until they were uniformly mixed. Then, concentrated hydrochloric acid was added dropwise to the beaker under stirring to adjust the pH value to 5. The mixture was poured into a dry three-necked flask and heated to 65°C with stirring. Anhydrous ethanol and coupling agent were evenly mixed and then slowly added to the three-necked flask. After the addition was completed, heating and stirring were continued at 65°C for 10 hours. Finally, the mixture was cooled to room temperature, and the mixture was filtered and washed with anhydrous ethanol for 5 times. After washing, the product was vacuum dried at 80°C for 12 hours to obtain a modified filler.
[0007] Furthermore, the inorganic filler is a compound of nano titanium dioxide, montmorillonite, conductive carbon black and tourmaline powder in a mass ratio of 2:3:10:1.
[0008] Furthermore, the coupling agent is one or more of dodecyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, and 3-(methacryloyloxy)propyltrimethoxysilane.
[0009] Furthermore, the coupling agent is prepared by compounding dodecyltrimethoxysilane and vinyltrimethoxysilane in a mass ratio of 1:1-3.
[0010] Furthermore, the mass ratio between the inorganic filler and the coupling agent is 15-20:1.
[0011] Furthermore, the plasticizer is one or more of diisononyl cyclohexane 1,2-dicarboxylate, dioctyl sebacate, and epoxy soybean oil.
[0012] Furthermore, the auxiliary agent is prepared by the following steps: S1. Under nitrogen protection, 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, DBU (1,8-diazobisspiro[5.4.0]undec-7-ene) and methanol were added to a dry three-necked flask, stirred evenly and heated to 60°C, then slowly added a mixed solution of 3-butene-1-amine and methanol, and after the addition was completed, the mixture was kept at 60°C for 48 hours. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure to obtain intermediate 1; the dosage ratio of 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, 3-butene-1-amine, DBU and methanol was 23.3mL:13.3g:1.3mL:130mL; Under the catalytic action of DBU, the molar ratio of 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane to 3-butene-1-amine is controlled to be 1:2.05-2.1, and 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane and 3-butene-1-amine undergo Michael addition reaction. The reaction process is shown below:
[0013] S2. Add intermediate 1, triethylamine and DMSO (dimethyl sulfoxide) to a dry three-necked flask under nitrogen protection, stir and dissolve, then heat to 70°C, slowly add a mixed solution of 2,6-di-tert-butyl-4-bromomethylphenol and DMSO, keep warm at 70°C for 6 hours after the addition is complete, and distill under reduced pressure after the reaction to obtain intermediate 2; the amount ratio of intermediate 1, 2,6-di-tert-butyl-4-bromomethylphenol, triethylamine and DMSO is 24.2g:32.2g:16.7mL:200mL; Triethylamine is used as an acid-binding agent to control the molar ratio of intermediate 1 and 2,6-di-tert-butyl-4-bromomethylphenol to be 1:2.1-2.2. Under heating, -NH- of intermediate 1 and -Br of 2,6-di-tert-butyl-4-bromomethylphenol undergo substitution reaction. The reaction process is shown below:
[0014] S3. Under nitrogen protection, add intermediate 2, triethylamine and DMF (N,N-dimethylformamide) to a dry three-necked flask, stir to dissolve, then heat to 80°C, slowly add tetradecyl chloride, then keep at 80°C for 4 hours, and distill under reduced pressure after the reaction to obtain an auxiliary agent; the dosage ratio of intermediate 2, tetradecyl chloride, triethylamine and DMF is 27.6g:17.7mL:12.5mL:180mL.
[0015] Triethylamine is used as an acid binding agent to control the molar ratio of intermediate 2 to tetradecyl chloride to be 1:2.1-2.2. Under heating, the tertiary amine group of intermediate 2 and the -Cl of tetradecyl chloride undergo a substitution reaction. The reaction process is as follows:
[0016] The auxiliary agent of the present invention contains quaternary ammonium salt groups. The antibacterial mechanism of quaternary ammonium salts is mainly attributed to their positive charges. These positive charges combine with negatively charged genes on the cell wall of microorganisms to destroy the cell wall, resulting in bacteriolysis and cell death; in addition, quaternary ammonium salts can also denature proteins and cause cell death, destroy the semipermeability of cell membranes, and reduce the nutrient intake to maintain life; the mechanism of action of quaternary ammonium salts also includes adsorption and penetration into cell membranes, causing disorder in the cell membrane structure, leading to leakage of small molecules in cells, and then protein and nucleic acid degradation, and finally self-lytic enzymes causing cell disintegration until death. At the same time, the quaternary ammonium salt of the present invention contains a long carbon chain (14 carbons), which further enhances the antibacterial effect of the auxiliary agent. In addition, as a kind of cationic surfactant, quaternary ammonium salts can effectively absorb moisture in the air due to their special chemical structure and properties, thereby showing excellent antistatic effect. Therefore, the auxiliary agent of the present invention is added to the automotive interior PVC material to effectively prevent the interior material from getting moldy and has an antistatic effect, which can play a protective role.
[0017] The additive contains hindered phenol structure. The hindered phenol structure can provide hydrogen atoms to free radicals to terminate the chain reaction, or directly combine with active free radicals to form new relatively stable free radicals, thereby destroying any step in the free radical reaction process, playing a protective role, and maintaining the appearance and mechanical properties of automotive interior PVC materials. Therefore, the addition of additives can effectively prevent the fading, yellowing, hardening and cracking of automotive interior PVC materials and extend their service life.
[0018] The additives are rich in fluorine atoms, which have strong hydrophobicity. Adding additives rich in fluorine atoms into automotive interior PVC materials can improve the waterproof and moisture-proof properties of PVC materials.
[0019] The additive also contains multiple unsaturated double bonds, which can react chemically with the double bonds in the modified filler and the unreacted double bonds in the PVC resin under the action of the cross-linking agent. Therefore, a mutually cross-linked three-dimensional network structure is formed between the additive, the modified filler and the PVC resin. This structure can make the additive and the modified filler highly dispersed and stably present in the PVC material and give full play to their functions, thereby increasing the antibacterial, anti-aging, waterproof and moisture-proof and antistatic properties of the PVC material. This structure can also enhance the thermal stability and mechanical strength of the PVC material.
[0020] Furthermore, the stabilizer is one or more of an organic tin heat stabilizer and a rare earth stabilizer.
[0021] Furthermore, the processing aid is one or more of acrylic ester copolymers.
[0022] Furthermore, the cross-linking agent is one or both of dicumyl peroxide and dibenzoyl peroxide.
[0023] A method for preparing an antistatic automobile interior PVC material comprises the following steps: Weigh each raw material by weight and add it into a high-speed mixer. After mixing evenly, send it into a twin-screw extruder. After melt extrusion, cool it and cut it into pellets to obtain the antistatic automobile interior PVC material.
[0024] The invention has the beneficial effects that the additive contains quaternary ammonium salt groups, hindered phenol structures and abundant fluorine atoms, and the additive, modified filler and PVC resin all have chemical reactions with each other, so that a cross-linked three-dimensional network structure is formed between the additive, modified filler and PVC resin, so that the additive and modified filler can be fully dispersed and stably present in the PVC material, and can fully play their roles, thereby giving the automotive interior PVC material of the invention high-efficiency and lasting antibacterial, anti-aging, waterproof and moisture-proof, antistatic and other properties. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1 The specific steps for preparing the modified filler are as follows: 8g of nano titanium dioxide, 12g of montmorillonite, 40g of conductive carbon black, 4g of tourmaline powder and 250mL of deionized water were fully stirred in a 500mL beaker until mixed evenly, and then concentrated hydrochloric acid was added dropwise to the beaker under stirring to adjust the pH value to 5, and then poured into a 500mL dry three-necked flask, stirred and heated to 65°C, 10mL of anhydrous ethanol, 1.6g of vinyltriethoxysilane and 1.6g of 3-(methacryloyloxy)propyltrimethoxysilane were mixed evenly and then slowly added to the above three-necked flask, and after the addition was completed, heating and stirring were continued at 65°C for 10h, and finally cooled to room temperature, the mixture was filtered, washed with anhydrous ethanol 5 times, and after washing, the product was vacuum dried at 80°C for 12h to obtain a modified filler.
[0027] Example 2 The specific steps for preparing the modified filler are as follows: 8g of nano titanium dioxide, 12g of montmorillonite, 40g of conductive carbon black, 4g of tourmaline powder and 250mL of deionized water were fully stirred in a 500mL beaker until mixed evenly, and then concentrated hydrochloric acid was added dropwise to the beaker under stirring to adjust the pH value to 5, and then poured into a 500mL dry three-necked flask, stirred and heated to 65°C, 10mL of anhydrous ethanol, 1.8g of dodecyltrimethoxysilane and 1.8g of vinyltrimethoxysilane were mixed evenly and then slowly added to the above three-necked flask, and after the addition was completed, heating and stirring were continued at 65°C for 10h, and finally cooled to room temperature, the mixture was filtered, washed with anhydrous ethanol 5 times, and after washing, the product was vacuum dried at 80°C for 12h to obtain a modified filler.
[0028] Example 3 The specific steps for preparing the modified filler are as follows: 8g of nano titanium dioxide, 12g of montmorillonite, 40g of conductive carbon black, 4g of tourmaline powder and 250mL of deionized water were fully stirred in a 500mL beaker until mixed evenly, and then concentrated hydrochloric acid was added dropwise to the beaker under stirring to adjust the pH value to 5, and then poured into a 500mL dry three-necked flask, stirred and heated to 65°C, 10mL of anhydrous ethanol, 1.07g of dodecyltrimethoxysilane and 3.23g of vinyltrimethoxysilane were mixed evenly and then slowly added to the above three-necked flask, and after the addition was completed, heating and stirring were continued at 65°C for 10h, and finally cooled to room temperature, the mixture was filtered, washed with anhydrous ethanol 5 times, and after washing, the product was vacuum dried at 80°C for 12h to obtain a modified filler.
[0029] Example 4 Preparation of auxiliary agent, the specific steps are as follows: S1. Under nitrogen protection, 23.3 mL of 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, 1.3 mL of DBU and 130 mL of methanol were added to a 250 mL dry three-necked flask, stirred evenly and heated to 60°C, then 13.3 g of a mixed solution of 3-butene-1-amine and methanol was slowly added, and after the addition was completed, the mixture was kept at 60°C for 48 hours. After the reaction was completed, it was cooled to room temperature and distilled under reduced pressure to obtain intermediate 1; S2. Under nitrogen protection, add 24.2 g of intermediate 1, 16.7 mL of triethylamine and 100 mL of DMSO to a 500 mL dry three-necked flask, stir and dissolve, then heat to 70°C, slowly add a mixed solution of 32.2 g of 2,6-di-tert-butyl-4-bromomethylphenol and 100 mL of DMSO, keep warm at 70°C for 6 h after the addition, and distill under reduced pressure after the reaction to obtain intermediate 2; S3. Under nitrogen protection, add 27.6 g of intermediate 2, 12.5 mL of triethylamine and 180 mL of DMF into a 500 mL dry three-necked flask, stir to dissolve and then heat to 80°C, then slowly add 17.7 mL of tetradecyl chloride, then keep the temperature at 80°C for 4 hours, and distill under reduced pressure after the reaction is completed to obtain an auxiliary agent.
[0030] Example 5 The specific steps for preparing automotive interior PVC materials are as follows: 90 parts of PVC resin, 10 parts of S85 thermoplastic polyurethane, 48 parts of modified filler prepared in Example 1, 30 parts of cyclohexane 1,2-diisononyl dicarboxylate, 2 parts of additives prepared in Example 2, 0.5 parts of XT-3 rare earth stabilizer, 0.5 parts of ACR-201 acrylic acid ester processing aid, and 0.05 parts of diisopropylbenzene peroxide were weighed by weight and added into a high-speed mixer, mixed evenly, and then sent to a twin-screw extruder. After melt extrusion, the mixture was cooled and pelletized to obtain an automotive interior PVC material.
[0031] Example 6 The specific steps for preparing automotive interior PVC materials are as follows: 96 parts of PVC resin, 17 parts of S85 thermoplastic polyurethane, 56 parts of modified filler prepared in Example 2, 20 parts of diisononyl cyclohexane 1,2-dicarboxylate, 15 parts of dioctyl sebacate, 3 parts of additives prepared in Example 2, 0.7 parts of di-n-octyltin dilaurate rare earth stabilizer, 0.7 parts of ACR-201 acrylic acid ester processing aid, and 0.08 parts of diisopropylbenzene peroxide were weighed by weight and added into a high-speed mixer, mixed evenly, and then fed into a twin-screw extruder. After melt extrusion, the mixture was cooled and pelletized to obtain an automotive interior PVC material.
[0032] Example 7 The specific steps for preparing automotive interior PVC materials are as follows: 100 parts of PVC resin, 20 parts of S85 thermoplastic polyurethane, 64 parts of modified filler prepared in Example 3, 20 parts of diisononyl cyclohexane 1,2-dicarboxylate, 10 parts of dioctyl sebacate, 10 parts of epoxidized soybean oil, 4 parts of the additive prepared in Example 2, 1 part of di-n-octyltin dilaurate rare earth stabilizer, 0.8 parts of ACR-201 type acrylate processing aid, and 0.1 parts of dibenzoyl peroxide are weighed by weight and added into a high-speed mixer, mixed evenly, and then fed into a twin-screw extruder. After melt extrusion, the mixture is cooled and pelletized to obtain an automotive interior PVC material.
[0033] Comparative Example 1 The specific steps for preparing automotive interior PVC materials are as follows: The remaining steps remained unchanged, except that the auxiliary agent in Example 5 was replaced by 1 part of antioxidant 1010 and 1 part of didodecyl dimethyl ammonium bromide antibacterial agent to prepare the automotive interior PVC material.
[0034] Comparative Example 2 The specific steps for preparing automotive interior PVC materials are as follows: The remaining steps remained unchanged, except that the modified filler in Comparative Example 1 was replaced by 6 parts of nano titanium dioxide, 9 parts of montmorillonite, 30 parts of conductive carbon black and 3 parts of tourmaline powder to prepare an automotive interior PVC material.
[0035] Comparative Example 3 The specific steps for preparing automotive interior PVC materials are as follows: The remaining steps remain unchanged, only the additives in Example 5 are removed, and the modified filler is replaced by 6 parts of nano titanium dioxide, 9 parts of montmorillonite, 30 parts of conductive carbon black, and 3 parts of tourmaline powder to prepare an automotive interior PVC material.
[0036] Performance Testing The automotive interior PVC materials prepared in Examples 5-7 and Comparative Examples 1-3 were prepared into corresponding samples according to GB / T 8948-2008, and subjected to tensile strength test, elongation at break test and surface resistivity test; and then dry-heat aged at 110°C for 120h, and the tensile strength and elongation at break were tested again to evaluate the anti-aging performance of the automotive interior PVC materials; Table 1
[0037] The antibacterial properties of the automotive interior PVC materials prepared in Examples 5-7 and Comparative Examples 1-3 were tested with reference to QB / T2591-2003 "Antibacterial Plastics - Antibacterial Performance Test Methods and Antibacterial Effects". The test results are shown in Table 2 below: Table 2
[0038] The automotive interior PVC materials prepared in Examples 5-7 and Comparative Examples 1-3 were cut into 1.5 cm 3 The small cubes were immersed in distilled water at 10℃ and 40℃ for 15 days respectively, and the changes in the morphology of the small cubes were observed. The test results are shown in Table 3 below: Table 3
[0039] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0040] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. An antistatic automobile interior PVC material, characterized in that: The invention comprises the following raw materials in parts by weight: 90-100 parts of PVC resin, 10-20 parts of thermoplastic polyurethane, 48-64 parts of modified filler, 30-40 parts of plasticizer, 2-4 parts of auxiliary agent, 0.5-1 part of stabilizer, 0.5-0.8 part of processing aid, and 0.05-0.1 part of cross-linking agent; Wherein, the auxiliary agent is prepared by the following steps: S1. Under nitrogen protection, 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, DBU and methanol were added to a flask, the temperature was raised to 60° C. with stirring, 3-butene-1-amine and methanol were added, the reaction was carried out at 60° C. for 48 h, the reaction was cooled, and the reaction was carried out under reduced pressure to obtain intermediate 1; S2. Add intermediate 1, triethylamine and DMSO to a flask under nitrogen protection, stir and heat to 70°C, add 2,6-di-tert-butyl-4-bromomethylphenol and DMSO, react at 70°C for 6h, and distill under reduced pressure to obtain intermediate 2; S3, under nitrogen protection, add intermediate 2, triethylamine and DMF into a flask, stir and heat to 80°C, add tetradecyl chloride, react at 80°C for 4h, and distill under reduced pressure to obtain an auxiliary agent; The modified filler is prepared by the following steps: Mix the inorganic filler and deionized water evenly, add concentrated hydrochloric acid to adjust the pH value to 5, pour into a flask, heat to 65°C, mix anhydrous ethanol and a coupling agent and add them into the flask, stir at 65°C for 10 hours, cool, filter, wash, and dry to obtain a modified filler.
2. The antistatic automobile interior PVC material according to claim 1, characterized in that: The usage ratio of 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, 3-butene-1-amine, DBU and methanol in step S1 is 23.3 mL:13.3 g:1.3 mL:130 mL; the usage ratio of intermediate 1, 2,6-di-tert-butyl-4-bromomethylphenol, triethylamine and DMSO in step S2 is 24.2 g:32.2 g:16.7 mL:200 mL; the usage ratio of intermediate 2, tetradecane chloride, triethylamine and DMF in step S3 is 27.6 g:17.7 mL:12.5 mL:180 mL.
3. The antistatic automobile interior PVC material according to claim 1, characterized in that: The inorganic filler is nano titanium dioxide, montmorillonite, conductive carbon black and tourmaline powder compounded in a mass ratio of 2:3:10:
1.
4. The antistatic automobile interior PVC material according to claim 1, characterized in that: The coupling agent is one or more of dodecyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, and 3-(methacryloyloxy)propyltrimethoxysilane.
5. The antistatic automobile interior PVC material according to claim 4, characterized in that: The coupling agent is prepared by compounding dodecyltrimethoxysilane and vinyltrimethoxysilane in a mass ratio of 1:1-3.
6. The antistatic automobile interior PVC material according to claim 1, characterized in that: The mass ratio between the inorganic filler and the coupling agent is 15-20:
1.
7. The antistatic automobile interior PVC material according to claim 1, characterized in that: The plasticizer is one or more of diisononyl cyclohexane 1,2-dicarboxylate, dioctyl sebacate, and epoxy soybean oil.
8. The antistatic automobile interior PVC material according to claim 1, characterized in that: The stabilizer is one or more of an organic tin heat stabilizer and a rare earth stabilizer.
9. The antistatic automobile interior PVC material according to claim 1, characterized in that: The processing aid is one or more of acrylic ester copolymers; the crosslinking agent is one or two of dicumyl peroxide and dibenzoyl peroxide.
10. The method for preparing an antistatic automobile interior PVC material according to claim 1, characterized in that: The following steps are involved: Weigh each raw material by weight and add it into a high-speed mixer. After mixing evenly, send it into a twin-screw extruder. After melt extrusion, cool it and cut it into pellets to obtain the antistatic automobile interior PVC material.
